ANALISIS KOMPARATIF BUKU TEKS MATEMATIKA SMA: MENELAAH SISTEM PENILAIAN DAN PEMANFAATAN BERDASARKAN KURIKULUM 2013 DAN KURIKULUM MERDEKA - Nur Inaya; Mawadda Warahma; Uspiani Usman; Arviana Azzahra; Takdirmin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to evaluate and compare the learning assessment systems and the utilization of senior high school (SMA) mathematics textbooks based on the 2013 Curriculum and the Merdeka Curriculum. The transition between these two curriculums has altered the pedagogical paradigm, specifically regarding how instructional materials are designed and implemented in classrooms. This research employs a qualitative approach with a literature study or content analysis method. The data sources consist of official mathematics textbooks for SMA issued by the Ministry of Education, Culture, Research, and Technology, along with relevant scientific articles. The analysis focuses on two main dimensions: the structure of assessment instruments (formative, summative, and higher-order thinking skills) and the adaptability of textbook utilization by teachers. The results of this study indicate that the 2013 Curriculum textbooks emphasize rigid and structured cognitive assessment models with scientific approaches. In contrast, the Merdeka Curriculum textbooks provide more flexible assessment instruments that support differentiated learning and the reinforcement of the Pancasila Student Profile. Furthermore, the utilization of Merdeka Curriculum textbooks demands greater pedagogical creativity from teachers to adapt materials to student characteristics. This study concludes that while the Merdeka Curriculum provides more adaptive space, teachers still require comprehensive guidance to optimize the assessment tools provided in the textbooks.